Modified Stoppa Approach For Concomitant Anterior And Posterior Pelvic Ring Fracture: A case report - Arif - Wibowo; Mohammad Zaim Chilmi (The Hip and Knee Journal, 2022)
BACKGROUNDModified Stoppa approach was performed to access the site of anterior column fracture instead of the Ilioinguinal approach to reduce morbidity.CASE SUMMARYA 24-year-old female suffered a serious traffic accident when she was riding a motor cycle collided with a car from the front and fell off when dodged a hole on the road. Then, the patient was beneath a moving car after falling. Several hours after accident at the hospital, she diagnosed as closed pelvic fracture of right superior inferior pubic rami and right sacroiliac joint disruption, closed fracture of right shaft femur. After improvement the condition in the ward, open reduction and internal fixation for the femoral fracture and for the pelvis fracture were performed using a modified stoppa approach to access the fracture site.CONCLUSION Treatment using the modified Stoppa approach was suitable for anterior column fracture, in which pelvic fractures were sufficiently exposed, the fracture was conveniently reduced, less complications occurred, and curative effect was satisfactory.